Fundamento Constitucional de la Responsabilidad Administrativa Disciplinaria: Una Mirada Crítica de la Regulación del Nuevo Régimen del Servicio Civil - Díaz Roncal, Kenny (2016)
In light of the plight of the vast Peruvian regime, in this article, the constitutional grounds of the disciplinary regime and sanctioned procedure will be discussed; and if the current regulation of the civil service law consistent with these fundamentals and the extensive regime of Peruvian labor laws in the legislative development focusing on those powers granted to authorities specifically with regard to the disciplinary measures and disciplinary proceedings.